Lectures on Shakespeare - Auden, Wystan H. 1907-1973 (Critical editions / W.H. Auden, 2019)
From one of the great modern writers, the acclaimed lectures in which he draws on a lifetime of experience to take the measure of Shakespeare's plays and sonnets "W. H. Auden, poet and critic, will conduct a course on Shakespeare at the New School for Social Research beginning Wednesday. Mr. Auden . . . proposes to read all Shakespeare's plays in chronological order." So the New York Times reported on September 27, 1946, giving notice of a rare opportunity to hear one of the century's great poets discuss at length one of the greatest writers of all time. Reconstructed by Arthur Kirsch, these lectures offer remarkable insights into Shakespeare's plays and sonnets while also adding immeasurably to our understanding of Auden